2020
DOI: 10.3390/agronomy10040597
|View full text |Cite
|
Sign up to set email alerts
|

Paecilomyces variotii as A Plant-Growth Promoter in Horticulture

Abstract: In the present study, P. variotii, an endophytic fungus isolated from plant roots from the Cabo de Gata Natural Park (Parque Nacional Cabo de Gata—Spain), was tested to determine the effect on the growth promotion of tomato and pepper seeds and seedlings. For these purposes, germination trials in a laboratory and two experiments in a commercial nursery and greenhouse conditions were performed. The P. variotii isolate has shown a high ability to produce siderophores and IAA, but low ability to solubilize P. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 60 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…Siderophore production limits the availability of iron for pathogens [ 75 , 99 ]. In vitro synthesis of hydroxamate and carboxylate siderophores, such as ferrirubin trihydroxamate, has been described mainly in P. lilacinus and P. variotii [ 15 , 100 , 101 , 102 , 103 , 104 ].…”
Section: Biological Control Mechanisms Of the Genus Paecmentioning
confidence: 99%
See 3 more Smart Citations
“…Siderophore production limits the availability of iron for pathogens [ 75 , 99 ]. In vitro synthesis of hydroxamate and carboxylate siderophores, such as ferrirubin trihydroxamate, has been described mainly in P. lilacinus and P. variotii [ 15 , 100 , 101 , 102 , 103 , 104 ].…”
Section: Biological Control Mechanisms Of the Genus Paecmentioning
confidence: 99%
“…Some in vivo studies show a direct effect on plant growth promotion after using Paecilomyces , [ 15 ] but also an indirect effect due to fungal disease control [ 72 ]. Yang et al [ 125 ] observed inhibited S. sclerotiorum mycelial growth and sclerotia germination and a reduced disease severity after using P. lilacinus on a rapeseed crop.…”
Section: Biological Control Of Diseases Caused By Phytopathogenic mentioning
confidence: 99%
See 2 more Smart Citations
“…A mixture of two kinds of substrates, one containing buckwheat husk (BH) and oat (O), the other containing BH and rice (R) were tested for the mass multiplication of TA and TS [31]. Different proportions of BH-O (90-10%, 80-20% and 70-30% v/v) and BH-R (90-10%, 80-20% and 70-30% v/v) were submerged in 30% v/v of water for 24 h. Each mixture was sterilised for 1 h at 125 • C twice on consecutive days.…”
Section: Mass Production Of Ta and Ts On Solid Substratesmentioning
confidence: 99%